The crisis of 1866 - Marc Flandreau; Stefano Ugolini (Graduate Institute of International and Development Studies, 2014)
The collapse of Overend Gurney and the ensuing Crisis of 1866 was a turning point in British financial history. The achievement of relative stability was due to the Bank of Englands willingness to offer generous assistance to the market in a crisis, combined with an elaborate system for maintaining the quality of bills in the market. We suggest that the Bank bolstered the resilience of the money market by monitoring leverage-building by money market participants and threatening exclusion from the discount window. When the Bank refused to bailout Overend Gurney in 1866 there was panic in the market. The Bank responded by lending freely and raising the Bank rate to very high levels. The new policy was crucial in allowing for the establishment of sterling as an international currency.
Keywords: E58; G01; N13; 330; Bagehot; bank of England; lending of last resort; supervision; moral hazard; discount; Overend Gurney Panic; baring